LEGAL RECONSTRUCTION OF INHERITED RICE FIELD MANAGEMENT RIGHTS IN BONE, SOUTH SULAWESI - Paikah, Nur; Fahri, Marjana (Institut Agama Islam Negeri Bone, 2023)
The existence of rights to the management of jointly inherited rice fields and the concept of legal reconstruction of the control of inherited rice fields is qualitative research; the approach used is social, legal research, data collection through interviews, observation, and documentation. Data analysis includes data reduction, data presentation, and conclusion drawing. The study results describe the management of jointly inherited rice fields using three systems: the individual inheritance system, the mayoral inheritance system, and the collective inheritance system, especially in the community where there is a habit of using the collaborative inheritance management system for rice fields. The management of the jointly inherited rice fields still exists where the rice fields are not sold only with an agreement that the inheritance will be received in turn with relatives and become a souvenir from the parents. Conflicts often arise because the collective inheritance system is carried out only verbally. Hence, there is a need for legal reconstruction to make a written agreement involving witnesses and the local government so that no party is harmed.